2010
DOI: 10.1111/j.1468-3083.2010.03814.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of benign cutaneous disease among Oxford renal transplant recipients

Abstract: In this first comprehensive study on prevalence of benign cutaneous diseases in a UK transplant population, a wide range of skin disorders was identified. It is therefore important that RTRs have access to dermatology services post-transplantation for appropriate management of benign cutaneous conditions as well as early detection of cutaneous malignancy and education regarding risks of sun exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 53 publications
3
24
1
4
Order By: Relevance
“…This finding is consistent with a previous study [6], but in apparent contrast with the fact that most patients of our series are receiving tacrolimus, commonly used to manage seborrhoeic dermatosis [28]. A possible explanation for this paradoxical behavior could be that only a percentage of seborrhoeic patients are full responders to tacrolimus [28], similarly to those affected by psoriasis [27].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This finding is consistent with a previous study [6], but in apparent contrast with the fact that most patients of our series are receiving tacrolimus, commonly used to manage seborrhoeic dermatosis [28]. A possible explanation for this paradoxical behavior could be that only a percentage of seborrhoeic patients are full responders to tacrolimus [28], similarly to those affected by psoriasis [27].…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, scant clinical data are available regarding the incidence of inflammatory skin diseases in patients with solid organ transplantation (Table 4). In a previous study performed to evaluate the incidence of cutaneous diseases in a group of 282 kidney transplant recipients, we reported that inflammatory conditions occur in 14.9% of patients [14], in agreement with previous studies [6,7]; an even lower occurrence of inflammatory diseases in transplanted patients was scored by [8], with only a few cases of acneiform eruptions, rosacea, asteatotic eczema, contact eczema and stasis dermatitis. Notably, the incidence of skin diseases with an immunologic pathogenesis is considered to be an even more uncommon event, with only a few sporadic cases reported [14,15].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations